سیاسی تنازعات کا اسلام میں تدارک : Resolution of Political Conflicts in Islam - Rashid, Abida; Abdul Rashid Qadri , Dr. (International Research Journal of Arabic and Islamic Studies, 2024)
Islam provides comprehensive guidelines for living, making it a complete code of life. The disputes we observe in the modern era can be resolved by referring to the numerous examples from the life of the Prophet Muhammad ﷺ. Additionally, the Quran contains many verses that provide clear instructions for resolving conflicts. The Prophet ﷺ not only eradicated disputes after the declaration of prophethood but also provided many examples of conflict resolution before his prophethood. Similarly, the concepts of forgiveness and retribution in the Quran both serve as means to prevent disputes. Belief in the oneness of God (Tawheed) in itself is a solution to many conflicts. The Quran teaches us to treat non-Muslims with kindness and not to resort to extremism in any matter. Furthermore, any issues that arise should be resolved through mutual consultation.